Experiences in Engaging the Public on Biotechnology Advances and Regulation - Quinlan, M. Megan; Smith, Joe; Layton, Raymond; Keese, Paul; Agbagala, Ma. Lorelie U.; Palacpac, Merle B.; Ball, Louise (Frontiers in Bioengineering and Biotechnology, 2016)
Public input is often sought as part of the biosafety decision making. Information and communication about the advances in biotechnology are part of the first step to engagement. This step often relies on the developers and introducers of the particular innovation, for example an industry funded website has hosted various authorities to respond to questions from the public. Alternative approaches to providing information have evolved, as demonstrated in Sub Saharan Africa where NGOs and associations play this role in some countries and subregions. Often times those in the public who choose to participate in engagement opportunities have opinions about the overall biosafety decision process. Case by case decisions are made within defined regulatory frameworks, however, and in general regulatory consultation does not provide the opportunity for input to the overall decision making process. The various objectives on both sides of engagement can make the experience challenging; there are no clear metrics for success. The situation is challenging because public input occurs within the context of the local legislative framework, regulatory requirements, and the peculiarities of the fairly recent biosafety frameworks, as well as of public opinion and individual values. Public engagement may be conducted voluntarily, or may be driven by legislation. What can be taken into account by the decision makers, and therefore what will be gathered and the timing of consultation, also may be legally defined. Several practical experiences suggest practices for effective engagement within the confines of regulatory mandates: (1) utilizing a range of resources to facilitate public education and opportunities for understanding complex technologies; (2) defining in advance the goal of seeking input; (3) identifying and communicating with the critical public groups from which input is needed; (4) using a clearly defined approach to gathering and assessing what will be used in making the biosafety decision; and (5) communicating using clear and simple language. These practices create a foundation for systematic methods to gather, acknowledge, respond to, and even incorporate public input. Applying such best practices will increase transparency and optimize the value of input from the public.